THE INFLUENCE OF LIFESTYLE AND ISLAMIC FINANCIAL LITERACY ON THE CONSUMPTIVE BEHAVIOR OF INDONESIA SMART SCHOLARSHIP FOR HIGHER EDUCATION SCHOLARSHIP RECIPIENTS - Tini, Munawar; Wadi, Ikhwan; Abu Hassan, Norhaslin (Ekonomi Islam, 2025)
Research Aims: This study aims to analyze the extent to which lifestyle and Islamic financial literacy influence the consumptive behavior of students receiving Indonesia Smart Scholarship for Higher Education assistance at the University of Gunung Rinjani. Design/Methodology/Approach: The study uses a quantitative approach with descriptive and verificative methods. Data were collected through questionnaires distributed to 100 students who are recipients of the Indonesia Smart Card for College Program. The data analysis was conducted using multiple linear regression, processed through SPSS version 26. Research Findings: The results indicate that lifestyle has a significant positive influence on consumptive behavior. Meanwhile, Islamic financial literacy has a significant negative influence. Simultaneously, lifestyle and Islamic financial literacy jointly contribute to consumptive behavior. These findings suggest that the higher the students' understanding of Islamic financial principles, the lower their tendency to engage in consumptive behavior. Theoretical Contribution/Originality: This research contributes to the development of literature in the field of Islamic behavioral finance by integrating lifestyle and Islamic financial literacy as predictors of consumptive behavior among scholarship recipients a group that has rarely been the focus of similar studies. Practitioners/Policy Implications: The findings highlight the importance for higher education institutions and policymakers to develop targeted Islamic financial literacy programs for scholarship recipients, in order to promote wiser financial behavior and reduce excessive consumption. Research Limitations/Implications: This study is limited to one institution and a relatively small sample size. Future research is recommended to include more universities and adopt a longitudinal approach to examine the consistency of the results over time.